Flexible Electrode Array System for Sweat Analysis in Vitro Information - Shao, Yichen (My University, 2022)
Sweat is a kind of liquid secreted to the body surface by human sweat glands, and its composition is highly related to the physiological state of the human body. Flexible wearable devices can dynamically monitor the change of sweat composition and the state of motion in real-time, which makes it become an important means for clinical and physiological research. In this thesis, a sensing system based on the flexible electrode array, which mainly includes a flexible electrode array and portable signal acquisition and processing system module, is designed and used for dynamic sweat detection. The system is characterized by high sensitivity, high selectivity, and repeatability, enabling online sweat composition analysis in vitro or wearable situations. Flexible electrode array mainly includes ion-selective electrodes (ISEs), enzyme electrodes, and reference electrodes. The ISEs include sodium and potassium selective electrodes. Enzyme electrodes include glucose and lactate oxidase electrodes. Reference electrodes are two pseudo-Ag/AgCl reference electrodes, both of which also act as counter electrodes. Signal acquisition and processing module mainly include voltage signal amplification, current signal amplification, filtering, signal selection, and A/D conversion circuit. This thesis studies the response characteristics of the electrode array to four kinds of sweat components. The sensitivity of ISEs and enzyme electrodes can be obtained by using an electrochemical workstation: The voltage response sensitivity of potassium ISE is 60.8 mV/lg[c(K+)]; The voltage response sensitivity of sodium ISE is 45.9 mV/lg[c(Na+)]; The current response sensitivity of glucose oxidase electrode is 2.28 μA·L/mmol; The current response sensitivity of lactate oxidase electrode is 45 nA·L/mmol. At the same time, the selectivity of ISEs is studied, and the experiment shows that both potassium and sodium ISE have a good anti-interference ability with low sensitivity against temperature. The sensitivity of potassium, sodium, glucose and lactate electrodes can still maintain a good linear relationship and meet the sensitivity requirements by using the portable signal acquisition and processing system. Combined with the "Clip Plate Method", sodium ion, glucose, and lactate of sweat sample collected from sportive volunteers are measured and analyzed, and the detecting of oxygen saturation and heart rate is also carried out in real-time, through which it can be found that the composition of sweat will change with the motion state and individual differences, providing a reference for the follow-up single targeted detection. In the thesis, a new type of enzyme electrode based on viologen compounds is developed, which has simple technological process and good stability, and the current response sensitivity of glucose and lactate oxidase electrode based on sulfhydryl viologen is measured as -0.234 μA·L/mmol and -41.7 nA·L/mmol, which shows improved linearity and stability compared with conventional enzyme electrode.
Keywords: flexible electrode array, sensing, ion-selective electrode, enzyme electrode, electrochemistry, sensitivity, circuit system, sweat composition, viologen